2017
DOI: 10.1002/jip.1478
|View full text |Cite
|
Sign up to set email alerts
|

Police officers' beliefs about, and use of, cues to deception

Abstract: Meta-analytic findings indicate that people, including police officers, are generally poor at detecting low-stakes deception. Related to this, investigations of behaviours that people reportedly use to make truth or lie judgements tend to conclude that people rely on incorrect stereotypes. However, consistent findings suggest that police officers are able to detect high-stakes deception; this implies that, at least in some contexts, police officers utilise reliable cues to deception. The research presented her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
1
4
0
2
Order By: Relevance
“…In contrast, participants in the No label condition perceived the defendant as a character who was lying for his own interests, based on his body language, difficulty recalling the event, and lack of eye contact. This is consistent with research showing that credibility assessments are often based on verbal and non-verbal behaviours such as eye contact (Wright and Wheatcroft 2017) twitchy and repetitive movements (e.g., Granhag et al 2004), demeanor (Levine et al 2011), and story-telling ability (DePaulo et al 2003).…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, participants in the No label condition perceived the defendant as a character who was lying for his own interests, based on his body language, difficulty recalling the event, and lack of eye contact. This is consistent with research showing that credibility assessments are often based on verbal and non-verbal behaviours such as eye contact (Wright and Wheatcroft 2017) twitchy and repetitive movements (e.g., Granhag et al 2004), demeanor (Levine et al 2011), and story-telling ability (DePaulo et al 2003).…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with the Leakage Account, variance in accuracy rates among high-stakes observers could be due, in part, to variance in observers’ abilities to perceive and understand the meaning of targets’ verbal and nonverbal behaviors and to use them diagnostically. This process likely draws on cognitive and emotional resources (Wojciechowski, Stolarski, & Matthews, 2014), and so individual differences in these relevant resources may contribute, especially as accurate judgments may rely on integrating and understanding how targets’ behaviors relate to each other in internally (in)consistent ways (DePaulo et al, 2003; Wright & Wheatcroft, 2017). However, little research has consistently shown what personal factors might support accurate detection (Aamodt & Custer, 2006), and even less has investigated the contribution of specific cognitive and emotional resources.…”
Section: What Individual Differences Might Support Truth and Deceptiomentioning
confidence: 99%
“…Jurors often base witness credibility assessments on a witness' verbal and non-verbal behaviours such as eye contact (Wright & Wheatcroft, 2017), twitchy and repetitive movements (e.g., Granhag, Andersson, Strömwall, & Hartwig, 2004), demeanor (Levine et al, 2011), surface features of speech such as pitch and intonation (Granhag et al, 2004;Ozuru & Hirst, 2006), and story-telling ability (DePaulo et al, 2003)all of which can be atypical in autistic individuals (e.g., de Marchena & Eigsti, 2010;Loveland et al, 1994;Peppé, McCann, Gibbon, O'Hare, & Rutherford, 2007;Senju & Johnson, 2009). Critically, however, while first impressions of autistic adults are often less favourable, several studies have recently reported that informing observers of an individual's autism diagnosis results in observers attributing the individual's behaviours to their autism, instead of using the behaviours as a basis for making more negative judgements about them as individuals in everyday contexts.…”
mentioning
confidence: 99%